Guiding Quranic Readings and Protesting for them and their Impact on Interpretation - Zwer , Amal (Islamic Sciences Journal, 2023)
ABSTRACT The research aims to demonstrate the extent to which the nation’s scientists care about the science of directing Qur’anic readings, ancient and modern, because of its great importance in explaining the reasons for the readers’ choices and protesting for them, especially the frequent ones, as most of them revolve around linguistic, syntactic and rhetorical issues, as well as the transmission of the Qur’an and Sunnah. I adopt in this study on the descriptive and analytical approach, as well as the synthesis approach, to know the differences of readers in the words of the Qur’an, The following are the most important results directing Qur’anic readings, especially the frequent ones, has a significant impact on enriching the Arabic language with many meanings and linguistic expressions that highlight the miracles and eloquence of the Qur’an. In addition to that, state responses to the objections of some linguists and grammarians, for the original is the Noble Qur’an, and the syntax rules are set according to the correct readings. The protest against the readings highlights the languages ​​of the Arabs, and what has disappeared from its dialects, and there is a response to everyone who tried to question the Qur’anic text from Atheists and Orientalists at the present time.